The relationship of gender differences to social development.: It is an analytical theoretical study (Raparin Journal of Humanities (RJH), 2024)
The main purposes of this study are to demonstrate the relationship between gender differences and social development. This study relies on theories (biology, social roles and gender differences) and the factors that underlie gender differences to analyze this relationship, through the use of descriptive analytical methods. The most important conclusions that this study achieved are: There is a wide gender gap in human society in terms of roles, especially in Kurdish society.  Gender differences were also based on culture, political power, education and family, which are important social development agencies.  There is also an inverse exchange relationship between gender differences and social development, as much as the differences will be extended, social development will be narrowed.